National model of the “class teacher” in secondary schools of Uzbekistan - Khonturaeva Nargiza Khaidarovna (Peerian Journals Publishing, 2024)
This article describes methods of working with students by class teachers of secondary schools through innovative methods. The duties and responsibilities of the class leader to students are shown. It is envisaged that students will carry out their educational work together with their parents
Keywords: Culture; skill; personality; education